Echocardiographic pattern of heart diseases in a North - Western Nigerian tertiary health institution - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Transthoracic Echocardiography is an important non-invasive technique which provides information about cardiac structure and function, thus useful in the evaluation and management of cardiac diseases. Previous studies on echocardiography findings in our environment documented Hypertensive heart disease, Dilated Cardiomyopathy and Rheumatic Heart Disease as the commonest findings in patients with cardiac diseases. This study aimed to provide an update on the common echocardiography findings in this part of the country since previous studies were done over a decade ago.Materials and Methods:We reviewed echocardiographic reports of 1012 consecutive patients aged ≥15 years from September 2011 to August 2014 (3 years). The reports were reviewed for demographic parameters, indications for the procedure and main echocardiography diagnoses.Results:The mean age of the 1,012 individuals studied was 41.28 ± 16.25 years. There were 330 males and 682 females. The commonest clinical indication for echocardiography was Systemic hypertension/Hypertensive heart disease (41%) followed by Peripartum cardiomyopathy (20%) and Congestive cardiac failure (12%) of unknown cause. The most prevalent echocardiographic diagnoses was Hypertensive heart disease seen in 40.3%, followed by Peripartum cardiomyopathy (32%), Dilated cardiomyopathy (5.9%), and Rheumatic heart disease 4.6%. Normal echocardiographic findings were seen in 14.9% of the subjects.Conclusion:Hypertensive heart disease remains the most common echocardiographic indication and diagnosis. Peripartum cardiomyopathy was frequent in our centre and this may be related to the increased availability and accessibility to echocardiographic facility as well as the low socioeconomic status of the category of patients that attend the centre.